Uremic pneumonitis in an eight-month-old canine – Case report (Research, Society and Development, 2022)
The kidneys are organs responsible for the homeostasis of the organism, through hydroelectrolytic balance and their role in excretion and reabsorption. These organs are subject to injury caused by toxic, infectious or ischemic agents. Acute kidney injury (AKI) is responsible for numerous complications in the body, with repercussions on various organs, such as the lungs, which can lead to increased vascular permeability. Uremic pneumonitis results from changes in pulmonary vascular permeability secondary to uremia in dogs with AKI. The objective of this work was to report a case of uremic pneumonitis in a puppy. The main complaint reported by the tutor was prostration, starting a few days after the surgical procedure. On physical examination, dyspnea, increased systemic systolic blood pressure, and respiratory auscultation with a discontinuous harsh noise were observed. In performing T-FAST, comet tail patterns were evidenced and, on radiography, bronchial, interstitial and alveolar patterns were observed in lung fields. The patient was admitted for supportive care. After admission to the hospital, blood count was performed and biochemical enzymes were measured, as well as electrolytes, showing uremia, hyperphosphatemia, hyperkalemia, leukocytosis and polycythemia. During follow-up of the patient, sinus bradycardia was observed, and he was hospitalized, under nasal tube for oxygen supply, gastric tube for food supply and medication for support. Lung injury would be best described by histopathological examination. Therefore, the present work reinforces the importance of early diagnosis of AKI and the resulting systemic changes, related to rapid intervention to guarantee the patient's survival.